Determining The Role of Ion Exchange in Permeability Alteration During Asp Injection: A Laboratory-Scale Study Using Cmg Reactive Transport Modeling - Dike Fitriansyah Putra; Mohd Zaidi Jaafar; Tengku Amran Tengku Mohd; Novia Rita; Agus Dahlia; Ichsan Al Sabah Lukman; M. Haidar T. Putra (Testing Center for Oil and Gas LEMIGAS, 2025)
Electrokinetic-based Enhanced Oil Recovery (EK-EOR) presents a novel method that applies electric fields to mobilize trapped hydrocarbons in formations with low permeability. This work investigates the impact of ion exchange and mineralogical reactions on permeability behavior during Alkali-Surfactant-Polymer (ASP) flooding, integrating laboratory-scale sand-pack experiments with reactive transport simulation in CMG-GEM. During ASP injection, a marked rise in differential pressure indicated abrupt changes in permeability caused by polymer accumulation, mineral dissolution, and early-stage ion exchange. Two numerical scenarios were assessed: one involving only aqueous-phase chemistry, and another incorporating fluid reactions and solid-surface ion exchange. The latter case required minimal calibration to match experimental data, while the former demanded unrealistic permeability upscaling. The results underscore ion exchange as a vital mechanism influencing fluid transport in EK-EOR. Although wettability alteration is often associated with ASP processes, this study suggests that under short exposure periods, changes in permeability dominate recovery performance. The findings improve reservoir modeling by promoting geochemical integration into simulation workflows.